Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

Evaluate the expression without using a calculator.

ln* square root of e^4 - square root of lne^4


Sagot :

sqrt(e^4) = e^2
ln[sqrt(e^4)] = ln[e^2] = 2ln[e] = 2
sqrt[ln(e^4)] = sqrt[4ln(e)] = sqrt[4] = 2
2 - 2 = 0.

Answer: 4

Step-by-step explanation:

answer on edg 2020.

Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.